2013
DOI: 10.1111/jiec.12072
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of a Lithium‐Ion Battery Vehicle Pack

Abstract: Electric vehicles have no tailpipe emissions, but the production of their batteries leads to environmental burdens. In order to avoid problem-shifting, a life cycle perspective should be applied in the environmental assessment of traction batteries. The goal of this study is to provide a transparent inventory for a lithium-ion nickel-cobalt-manganese traction battery based on primary data and to report its cradle-to-gate impacts. The study was carried out as a processbased attributional life cycle assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
512
4
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 509 publications
(574 citation statements)
references
References 22 publications
(61 reference statements)
13
512
4
4
Order By: Relevance
“…Furthermore, LMR also has a high voltage and specific capacity that allows for a significant increase in energy density over current commercially available cathode materials 102 . Despite these advantages, poor rate capability 103 result in low power density, whereas thermal safety issues 37 and voltage fade 104 result in poor lifetime and stability, all of which complicate its commercial introduction for EVs. Lithium iron phosphate (LFP) is found in nature as the mineral triphylite 105 and has low exposure risks or hazards 86 .…”
Section: Cathode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, LMR also has a high voltage and specific capacity that allows for a significant increase in energy density over current commercially available cathode materials 102 . Despite these advantages, poor rate capability 103 result in low power density, whereas thermal safety issues 37 and voltage fade 104 result in poor lifetime and stability, all of which complicate its commercial introduction for EVs. Lithium iron phosphate (LFP) is found in nature as the mineral triphylite 105 and has low exposure risks or hazards 86 .…”
Section: Cathode Materialsmentioning
confidence: 99%
“…As a bulk material, LFP has moderate electric potential 47 , outstanding thermal stability 52 , and excellent cycling performance 106 , but its two-phase reaction mechanism, with low ion diffusion rate and very low electronic conductivity 107 , makes it difficult to reach capacities close to the theoretical limit 52 . However, research found that in nanoparticle form, the material could produce stable cycling much closer to its theoretical capacity because the phase diagram is changed and the reaction proceeds via a metastable single-phase mechanism 37 . This development increased the material's energy- 52 and power 33 densities, but its energy density remained inferior to that of other commercially available cathode materials such as NMC 47,48 .…”
Section: Cathode Materialsmentioning
confidence: 99%
“…These varieties were not mainly due to different Li-ion chemistries but due to different modelling approaches (top down vs. bottom up). In a more recent and comprehensive study, Ellingsen et al (2014) reviewed results between 38 and 338 kg CO 2 eq/kWh for the production of the battery, and added 172-487 kg CO 2 eq/kWh from their own study. It was decided here to calculate a mean from Ellingsen et al's (2014) data giving a figure of 168 kg CO 2 eq/kWh.…”
Section: Ghg Emissions Of Battery Electric Vehicles the Hybrid Wtw+lmentioning
confidence: 99%
“…This study uses data from Ellingsen et al (2014), and is based on primary data for a traction battery cell. Ellingsen's medium 'ASV' value of 960 MJ/kWh was used, which is representative of the broader literature [e.g.…”
Section: Embodied Energy Of Vre and Storagementioning
confidence: 99%